Green fusion proteins: An approach to sustainable nutrition blending plant and algae-based proteins for a circular food system - Surumpa Jareonsin; Chayakorn Pumas; Daranrat Jaitiang; Toungporn Uttarotai (Future Foods)
Combining plant-based proteins with valuable algae-based proteins offers a solution to various social, economic and environmental challenges, contributing to a more sustainable and equitable world. Plants play a crucial role in poverty reduction by generating income opportunities and addressing hunger. However, producing plant-based meat alternatives involves overcoming challenges such as allergen concerns, processing techniques, consumer acceptance and lower nutritional quality. Algae, while contributing significantly to economic and sustainability goals, face limitations in exclusively mimicking meat products on its own. Blending algae with plant-based proteins presents a promising way for improving alternative protein characteristics and mimicking meat more effectively. The combination of two green bioresources as alternative proteins offers a nutritionally superior and environmentally friendly alternative, poised to transform food production and consumption with positive impacts on the environment and human health. This review provides a comprehensive understanding of alternative protein sources, focusing on incorporating algae into plant-based products. It explores emerging technologies in alternative protein production, examining the potential of using algae as a platform for expressing phytochemicals, particularly from plants. The integration of these two alternative green protein sources aligns with the circular model, ensuring a sustainable food system with reduced environmental impact.